The Role of Self-Stigma in Individuals with Psychological Disorders on Help-Seeking Behavior for Professional Psychological Services among University Students in Bali - Theresia Aurelia; Made Padma Dewi Bajirani (Badan Penerbit STIEPARI Press, 2025)
Mental health is a crucial component in supporting individual well-being, particularly for university students who are often faced with various stressors. Despite the increasing accessibility of mental health services, several barriers still prevent individuals from seeking help, one of which is self-stigma. Self-stigma is a process in which individuals internalize society’s negative perceptions about mental health. This study aims to identify the role of self-stigma in influencing help-seeking behavior for professional psychological services among university students in Bali. A quantitative approach was employed, utilizing simple linear regression analysis. A total of 129 university students (female = 101; mean age = 18–25 years) from various higher education institutions in Bali participated in the study through purposive sampling. Data collection instruments consisted of two scales: the Self-Stigma Scale with a reliability coefficient of 0.934, and the Psychological Help-Seeking Behavior Scale with a reliability coefficient of 0.871. Data were analyzed using simple linear regression. The results showed an R Square value of 0.536, indicating that self-stigma contributes 53.6% to help-seeking behavior. The findings reveal that self-stigma negatively affects students’ behavior in seeking psychological help. Although students are increasingly aware of the importance of professional mental health support, this awareness is not yet fully reflected in their actions. Therefore, continuous efforts are needed to reduce self-stigma through educational campaigns. Students are also expected to serve as agents of change in broader social contexts by promoting a positive culture of psychological help-seeking within society.